The cracks in the melting pot: community, nation and gender in Ada María Elflein and Salvadora Medina Onrubia (Anclajes, 2025)
Although the literary trajectories of Ada María Elflein and Salvadora Medina Onrubia seem to be antagonistic in the context of Argentina’s centenary, the short stories that they published in those years share an unexpected link: they are fictions in which the notion of people and the characters of popular extraction play a fundamental role associated with the reflection on Argentine identity. The image of the melting pot of races, the patriotic past and the gender tensions that these processes trigger in the configuration of the national community constitute key aspects in these stories in the face of the emergence of the nationalist discourse and the conflicts derived from the modernizing process in the Argentina of the first decades of the 20th century. Thus, Elflein and Medina Onrubia establish a tacit alliance that discusses the virile view associated with the Creole world and exposes the fissures of that Argentina that thinks itself modern.
Keywords: Ada María Elflein; Salvadora Medina Onrubia; Argentine literature; Mass culture; Nationalism